Proprotein Convertase 5/6 Is Critical for Embryo Implantation in Women: Regulating Receptivity by Cleaving ebp50 Modulating Ezrin Binding, and Membrane-Cytoskeletal Interactions - Velasquez, L (2011)
Establishment of endometrial receptivity is vital for successful embryo implantation; its failure causes infertility. Epithelial receptivity acquisition involves dramatic structural changes in the plasma membrane and cytoskeleton. Proprotein convertase 5/6 (PC6), a serine protease of the proprotein convertase (PC) family, is up-regulated in the human endometrium specifically at the time of epithelial receptivity and stromal cell decidualization. PC6 is the only PCmembertightly regulated in this manner. The current study addressed the importance and mechanisms of PC6 action in regulating receptivity in women. PC6 was dysregulated in the endometrial epithelium during the window of implantation in infertile women of three demographically different cohorts. Its critical role in receptivity was evidenced by a significant reduction in mouse blastocyst attachment of endometrial epithelial cells after PC6 knockdown by small interfering RNA. Using a proteomic approach, we discovered that PC6 cleaved the key scaffolding protein, ezrin-radixin-moesin binding phosphoprotein 50 (EBP50), thereby profoundly affecting its interaction with binding protein ezrin (a key protein bridging actin filaments and plasma membrane), EBP50/ezrin cellular localization, and cytoskeleton-membrane connections. We further validated this novel PC6 regulation of receptivity in human endometrium in vivo in fertile vs. infertile patients. These results strongly indicate that PC6 plays a key role in regulating fundamental cellular remodeling processes, such as plasma membrane transformation and membrane-cytoskeletal interface reorganization. PC6 cleavage of a crucial scaffolding protein EBP50, thereby profoundly regulating membrane-cytoskeletal reorganization, greatly extends the current knowledge of PC biology and provides substantial new mechanistic insight into the fields of reproduction, basic cellular biology, and PC biochemistry. Copyright © 2011 by The Endocrine Society.